Low-radiation coated glass, preparation method thereof, double-cavity hollow glass and application
By designing low-emissivity coated glass and using vacuum magnetron sputtering to deposit multiple layers of film, the compatibility issue between the transmittance and heat resistance of high-transmittance and high-performance Low-E glass in buildings is resolved, achieving excellent thermal insulation and high transmittance effects, and meeting ultra-low energy consumption requirements.
Patent Information
- Application Number
- CN202510911346.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-02
- Publication Date
- 2025-09-26
AI Technical Summary
The existing high-transmittance and high-performance Low-E glass made of three-glass two-cavity insulating glass cannot achieve both light transmittance and heat resistance and tempering performance in the construction industry, and the U value is too high to meet the requirements of ultra-low energy consumption.
A low-emissivity coated glass is designed, comprising a glass substrate and a laminated dielectric layer, an intermediate layer, an infrared reflective layer, a composite protective layer, and a shield layer. Each film layer is deposited by a vacuum magnetron sputtering method to ensure that the infrared reflective layer is not damaged, improve heat resistance and density, and optimize optical performance.
It achieves high transmittance, thermal insulation and heat resistance effects. The U value of the double-chamber insulating glass is ≤0.8, and the building shading coefficient SC is ≥0.60, meeting the requirements of ultra-low energy consumption, reducing energy loss in winter, reducing outdoor heat entry in summer, and maintaining good lighting.
Smart Images

Figure CN120698708A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of glass manufacturing, and in particular relates to a low-emissivity coated glass, a preparation method thereof, a double-cavity insulating glass and applications thereof. Background Art
[0002] Glass is widely used in architecture due to its excellent transparency, ability to transmit light and protect against wind and snow. With the development of modern science and technology, glass has been given even greater possibilities. High-transmittance, high-performance Low-E (low-emissivity) glass, with its high transparency and excellent energy-saving properties, is widely used in industrial glass applications such as transportation vehicles, trains, rail transit, and high-speed rail locomotives. It is particularly widely used in low-energy buildings and high-latitude regions. High-transmittance, high-performance Low-E glass has an extremely low U-value (heat transfer coefficient). Over 80% of infrared rays, invisible to the naked eye, are reflected by the glass, and far-infrared rays are almost completely reflected back, preventing them from penetrating. This significantly reduces the glass's UV transmittance. Its use in buildings can significantly reduce electricity consumption in residential and office buildings, saving on air conditioning and heating costs. Its use in freezers significantly reduces the load on air conditioning compressors, thereby reducing energy consumption.
[0003] However, the high-transmittance and high-performance Low-E glass currently produced on the market is made into three-glass two-cavity insulating glass and used in the construction industry. Its light transmittance cannot be combined with heat resistance and tempering properties.
[0004] Therefore, how to balance the tempering performance, heat resistance and light transmittance of low-emissivity coated glass and further reduce the U value of triple-glazed, two-chamber insulating glass to make it suitable for the construction industry is a technical problem that needs to be solved urgently. Summary of the Invention
[0005] In response to the shortcomings of the prior art, the present invention aims to provide a low-emissivity coated glass, a preparation method thereof, a double-cavity insulating glass, and applications. The low-emissivity coated glass designed by the present invention ensures that the infrared reflection layer is not damaged after tempering, improves the heat resistance of the low-emissivity film, and the surface emissivity of the low-emissivity film is as low as 0.036 after heat treatment. In addition, the density of the low-emissivity film is improved, the surface of the film is smoother and denser, and the hardness and antioxidant properties are excellent, showing good high-transmittance, thermal insulation and heat resistance effects. The double-cavity insulating glass prepared in this way has a visible light transmittance of ≥60%, a U value ≤0.8, and a building shading coefficient SC ≥0.60, meeting the requirements of ultra-low energy consumption and having good application potential.
[0006] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0007] In a first aspect, the present invention provides a low-emissivity coated glass, the low-emissivity coated glass comprising:
[0008] Glass substrate.
[0009] A low-emissivity film comprises a first dielectric layer, an intermediate layer, a second dielectric layer, an infrared reflecting layer, a composite protective layer, a third dielectric layer and a protective layer which are stacked in a direction away from the glass substrate.
[0010] The composite protective layer includes a first protective layer, a second protective layer, a third protective layer and a fourth protective layer which are stacked in a direction away from the infrared reflective layer.
[0011] The low-emissivity coated glass designed by the present invention ensures that the infrared reflective layer is not damaged after tempering, and improves the heat resistance of the low-emissivity film. The low-emissivity film can efficiently transmit visible and near-infrared light, but can achieve high reflection of medium and far-infrared light. After heat treatment, the surface emissivity of the low-emissivity film is as low as 0.036, which is equivalent to reflecting 96.4% of infrared heat, showing good high-transmittance, thermal insulation and heat resistance effects.
[0012] The present invention improves the density of the surface structure of the low-emissivity film and appropriately reduces the porosity of the film layer, making the surface of the low-emissivity film smoother and denser, and improving the hardness and oxidation resistance of the film layer.
[0013] The resulting double-chamber insulating glass has a U-value of ≤0.8 and a building shading coefficient (SC) of ≥0.60, providing excellent thermal insulation. This reduces energy loss in winter, lowering heating costs, and reduces outdoor heat ingress in summer, lowering cooling costs. Furthermore, its visible light transmittance is ≥60%, allowing more visible light to penetrate the window without affecting the field of view, ensuring excellent daylighting. Therefore, this double-chamber insulating glass meets ultra-low energy consumption requirements and has great potential for future applications.
[0014] It should be noted that the present invention does not limit the material of the glass substrate. For example, it can be ultra-white glass.
[0015] Preferably, the first dielectric layer includes a silicon nitride layer.
[0016] In the present invention, the silicon nitride layer serves as a dielectric layer, which helps to reduce heat transfer through the glass substrate, improve the thermal insulation effect, and enhance the bonding strength and stability of the film layer; it can also connect the glass substrate with other layers, improve the bonding performance of other layers with the glass substrate, and alleviate the internal stress of the low-emissivity film.
[0017] Preferably, the intermediate layer comprises a zinc tin oxide layer.
[0018] In the present invention, zinc tin oxide is used as the intermediate layer, has good chemical stability, high visible light transmittance, and can be well combined with the first dielectric layer and the second dielectric layer.
[0019] Preferably, the second dielectric layer includes an aluminum-doped zinc oxide layer.
[0020] In the present invention, the aluminum-doped zinc oxide layer serves as the second dielectric layer and can act as a seed layer for the infrared reflective layer, further optimizing the electrical properties of the infrared reflective layer. The aluminum-doped zinc oxide layer also has high light transmittance, providing a transparent base layer for the subsequent deposition of the infrared reflective layer. Furthermore, the aluminum-doped zinc oxide layer prevents atoms in the infrared reflective layer from diffusing into the glass substrate. It also prevents certain elements in the glass substrate from diffusing into the infrared reflective layer, thus avoiding degradation of film performance due to atomic diffusion and ensuring the structural and performance stability of each layer.
[0021] Preferably, the thickness of the first dielectric layer is 10-20 nm, for example, 10 nm, 12 nm, 14 nm, 16 nm, 18 nm or 20 nm.
[0022] Preferably, the thickness of the intermediate layer is 15-25 nm, for example, 15 nm, 20 nm or 25 nm.
[0023] Preferably, the thickness of the second dielectric layer is 6-10 nm, for example, 6 nm, 7 nm, 8 nm, 9 nm or 10 nm.
[0024] Preferably, the infrared reflective layer comprises a silver layer or a silver-based alloy layer. Exemplarily, the silver-based alloy layer may be an alloy layer formed by silver and at least one of gold, aluminum or copper.
[0025] Preferably, the thickness of the infrared reflective layer is 6-12 nm, for example, 6 nm, 7 nm, 8 nm, 9 nm, 10 nm, 11 nm or 12 nm.
[0026] Preferably, the first protective layer comprises a nickel-chromium layer.
[0027] In the present invention, the nickel-chromium layer serves as the first protective layer and has excellent oxidation resistance. During the process of tempering the low-emissivity coated glass, it can be partially oxidized as a protective layer of the infrared reflective layer. During the partial oxidation process, the visible light transmittance of the film layer will be improved, and the color will be more transparent.
[0028] Preferably, the second protective layer comprises an aluminum-doped zinc oxide layer.
[0029] Preferably, the third protective layer includes a nickel chromium oxide layer.
[0030] In the present invention, the nickel-chromium oxide layer serves as the third protective layer, has good chemical stability and corrosion resistance, and can protect the glass substrate and the internal film layer from corrosion by water vapor, oxygen, acid and alkali substances in the external environment, thereby ensuring the long-term performance stability of the low-emissivity coated glass; moreover, the nickel-chromium oxide layer can serve as a thermal stress buffer layer, which can alleviate the thermal stress caused by temperature changes to a certain extent, reduce the occurrence of cracking and shedding of the film layer, and improve the stability of the low-emissivity coated glass under different ambient temperatures.
[0031] Preferably, the fourth protective layer includes an aluminum-doped zinc oxide layer.
[0032] In the present invention, the second protective layer and the fourth protective layer can be made of the same type and have a high visible light transmittance, which is beneficial to further improve the overall light transmittance of the glass.
[0033] Preferably, the thickness ratio of the infrared reflective layer, the first protective layer, the second protective layer, the third protective layer and the fourth protective layer is (6-12): (0.5-1): (6-10): (0.3-0.8): (6-10), wherein the selection range of the infrared reflective layer "6-12" can be, for example, 6, 7, 8, 9, 10, 11 or 12, etc., the selection range of the infrared reflective layer "0.5-1" can be, for example, 0.5, 0.6, 0.7, 0.8, 0.9 or 1, the selection range of the infrared reflective layer "6-10" can be, for example, 6, 7, 8, 9 or 10, etc., the selection range of the infrared reflective layer "0.3-0.8" can be, for example, 0.3, 0.4, 0.5, 0.6, 0.7 or 0.8, etc., and the selection range of the infrared reflective layer "6-10" can be, for example, 6, 7, 8, 9 or 10, etc.
[0034] By optimizing the thickness of each film layer, this invention precisely controls the reflection, refraction, and interference of light between the layers, thereby achieving precise optimization of the optical properties of low-emissivity coated glass, helping to improve the light transmittance of subsequent products and reduce the U value. Furthermore, a reasonable thickness ratio helps form a more stable structure between the protective layers, ensuring a more uniform distribution of internal stress throughout the low-emissivity film, which helps reduce problems such as film cracking and shedding, and improves the film's stability and reliability during long-term use.
[0035] Preferably, the thickness of the first protective layer is 0.5-1 nm, for example, 0.5 nm, 0.6 nm, 0.7 nm, 0.8 nm, 0.9 nm or 1 nm.
[0036] Preferably, the thickness of the second protective layer and the fourth protective layer are independently 6-10 nm, for example, 6 nm, 7 nm, 8 nm, 9 nm or 10 nm.
[0037] Preferably, the thickness of the third protective layer is 0.3-0.8 nm, for example, 0.3 nm, 0.4 nm, 0.5 nm, 0.6 nm, 0.7 nm or 0.8 nm.
[0038] Preferably, the third dielectric layer includes a silicon nitride layer.
[0039] In the present invention, the silicon nitride layer serves as the third dielectric layer, has high hardness and good wear resistance, can improve the hardness of the glass surface, helps protect the infrared reflection layer and other functional layers from damage, and extends the service life of the low-emissivity coated glass; silicon nitride has good light transmittance in the visible light and near-infrared bands, and by adjusting parameters such as the thickness and refractive index of the silicon nitride layer, it can synergize with the infrared reflection layer, protective layer, etc. to optimize the optical properties of the coated glass; the silicon nitride layer can improve the interface bonding between different film layers, making the bonding between the film layers tighter and more uniform, thereby improving the structural stability, mechanical properties and impact resistance of the low-emissivity coated glass.
[0040] Preferably, the protective layer comprises a zirconium oxide layer.
[0041] In the present invention, the zirconium oxide layer has high hardness, excellent acid, alkali and weather resistance, excellent scratch resistance and other mechanical properties. Selecting this material as the protective layer has greater room for improvement in the reprocessing capacity of the overall coated glass.
[0042] Preferably, the thickness of the third dielectric layer is 20-30 nm, for example, 20 nm, 22 nm, 24 nm, 26 nm, 28 nm or 30 nm.
[0043] Preferably, the thickness of the protective layer is 4-8 nm, for example, 4 nm, 5 nm, 6 nm, 7 nm or 8 nm.
[0044] In a second aspect, the present invention provides a method for preparing the low-emissivity coated glass as described in the first aspect, the preparation method comprising the following steps:
[0045] A vacuum magnetron sputtering method is used to sequentially deposit a first dielectric layer, an intermediate layer, a second dielectric layer, an infrared reflection layer, a composite protective layer, a third dielectric layer and a protective layer on the surface of a glass substrate to form a low-emissivity film.
[0046] The composite protective layer includes a first protective layer, a second protective layer, a third protective layer and a fourth protective layer which are stacked in a direction away from the infrared reflective layer.
[0047] Preferably, the vacuum magnetron sputtering parameters of the intermediate layer include:
[0048] The target material is zinc tin oxide (for example, it can be composed of 52% ZnO and 48% SnO2), and the working gas includes an inert gas (for example, argon, etc.) and oxygen with a flow ratio of (12-16):1 (for example, it can be 12:1, 13:1, 14:1, 15:1 or 16:1, etc.), and the inert gas can be, for example, argon, etc.
[0049] Preferably, the vacuum magnetron sputtering parameters of the first dielectric layer and the third dielectric layer independently include:
[0050] The target material is a silicon aluminum alloy (for example, a rotating silicon aluminum target), and the working gas includes an inert gas (for example, argon, etc.) and nitrogen with a flow ratio of 9:(11-15) (for example, 9:11, 9:12, 9:13, 9:14 or 9:15, etc.).
[0051] Preferably, the vacuum magnetron sputtering parameters of the second dielectric layer include:
[0052] The target material is aluminum-doped zinc oxide, and the working gas includes an inert gas (such as argon) and oxygen with a flow ratio of (24-28):1 (such as 24:1, 25:1, 26:1, 27:1 or 28:1).
[0053] Preferably, the vacuum magnetron sputtering parameters of the infrared reflective layer include:
[0054] The target material is silver or a silver-based alloy, and the working gas is an inert gas (such as argon).
[0055] Preferably, the vacuum magnetron sputtering parameters of the protective layer include:
[0056] The target material is zirconium oxide, and the working gas includes an inert gas (such as argon) and oxygen with a flow ratio of (35-45):1 (such as 35:1, 40:1 or 45:1).
[0057] Preferably, the vacuum magnetron sputtering parameters of the first protective layer include:
[0058] The target material is a nickel-chromium alloy (for example, it may be composed of 20% Ni and 80% Cr), and the working gas is an inert gas (for example, it may be argon, etc.).
[0059] Preferably, the vacuum magnetron sputtering parameters of the second protective layer and the fourth protective layer independently include:
[0060] The target material is aluminum-doped zinc oxide, and the working gas includes an inert gas (such as argon) and oxygen with a flow ratio of (24-28):1 (such as 24:1, 25:1, 26:1, 27:1 or 28:1).
[0061] Preferably, the vacuum magnetron sputtering parameters of the third protective layer include:
[0062] The target material is a nickel-chromium alloy, and the working gas includes an inert gas (such as argon) and oxygen with a flow ratio of (4-9):1 (such as 4:1, 5:1, 6:1, 7:1, 8:1 or 9:1).
[0063] In a third aspect, the present invention provides a double-chamber insulating glass comprising a first glass, a second glass and a third glass, wherein a gas spacing layer is formed between the first glass and the second glass and between the second glass and the third glass.
[0064] Wherein, the second glass and the third glass are each independently the low-emissivity coated glass described in the first aspect, and the protective layer of the third glass is located on a side close to the second glass.
[0065] It should be noted that the first glass is ordinary glass, for example, float white glass.
[0066] In a fourth aspect, the present invention provides an application of the low-emissivity coated glass as described in the first aspect or the double-cavity insulating glass as described in the second aspect in the field of architecture or the field of new energy vehicles.
[0067] The numerical range described in the present invention includes not only the point values listed above, but also any point values between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0068] Compared with the prior art, the present invention has the following beneficial effects:
[0069] (1) The low-emissivity coated glass designed by the present invention ensures that the infrared reflective layer is not damaged after tempering, and improves the heat resistance of the low-emissivity film. The low-emissivity film can efficiently transmit visible and near-infrared light, but can achieve high reflection of mid- and far-infrared light. After heat treatment, the surface emissivity of the low-emissivity film is as low as 0.036, which is equivalent to reflecting 96.4% of infrared heat, showing good high-transmittance, thermal insulation and heat resistance effects.
[0070] (2) The present invention improves the density of the surface structure of the low-emissivity film and appropriately reduces the porosity of the film layer, making the surface of the low-emissivity film smoother and denser, and improving the hardness and anti-oxidation performance of the film layer.
[0071] (3) The U-value of the double-chamber insulating glass produced in this way is ≤0.8, and the building shading coefficient SC is ≥0.60, which can provide excellent thermal insulation. It can reduce energy loss in winter and lower heating electricity consumption. In summer, it can reduce outdoor heat entering the room and reduce cooling electricity consumption. At the same time, the visible light transmittance is ≥60%, indicating that more visible light can penetrate the window without affecting the observation field and providing good lighting. Therefore, the double-chamber insulating glass can meet the requirements of ultra-low energy consumption and has good application potential. BRIEF DESCRIPTION OF THE DRAWINGS
[0072] Figure 1 This is a schematic structural diagram of the low-emissivity coated glass provided in Example 1 of the present invention.
[0073] Among them, 1-glass substrate; 2-first dielectric layer; 3-intermediate layer; 4-second dielectric layer; 5-infrared reflection layer; 6-first protective layer; 7-second protective layer; 8-third protective layer; 9-fourth protective layer; 10-third dielectric layer; 11-protective layer. DETAILED DESCRIPTION
[0074] The technical solution of the present invention is further described below by way of specific embodiments. It should be understood by those skilled in the art that the embodiments are merely to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0075] Example 1
[0076] This embodiment provides a low-emissivity coated glass, the structural diagram of which is shown in FIG. Figure 1 As shown, the low-emissivity coated glass includes:
[0077] The glass substrate 1 is ultra-white glass.
[0078] A low-emissivity film, which includes a first dielectric layer 2, an intermediate layer 3, a second dielectric layer 4, an infrared reflection layer 5, a composite protective layer, a third dielectric layer 10 and a protective layer 11 stacked in a direction away from the glass substrate, and the composite protective layer includes a first protective layer 6, a second protective layer 7, a third protective layer 8 and a fourth protective layer 9 stacked in a direction away from the infrared reflection layer 5.
[0079] Among them, the first dielectric layer 2 is a silicon nitride layer, the intermediate layer 3 is a zinc tin oxide layer, the second dielectric layer 4 is an aluminum-doped zinc oxide layer, the infrared reflective layer 5 is a silver layer, the first protective layer 6 is a nickel-chromium layer, the second protective layer 7 is an aluminum-doped zinc oxide layer, the third protective layer 8 is a nickel-chromium oxide layer, the fourth protective layer 9 is an aluminum-doped zinc oxide layer, the third dielectric layer 10 is a silicon nitride layer, and the protective layer 11 is a zirconium oxide layer.
[0080] Among them, the thickness of the silicon nitride layer is 14nm, the thickness of the zinc tin oxide layer is 20nm, the thickness of the aluminum-doped zinc oxide layer is 8nm, the thickness of the silver layer is 8nm, the thickness ratio of the silver layer, nickel-chromium layer, aluminum-doped zinc oxide layer, nickel-chromium oxide layer and aluminum-doped zinc oxide layer is 8:0.6:8:0.3:8, the thickness of the silicon nitride layer is 25nm, and the thickness of the protective layer is 5nm.
[0081] This embodiment also provides a method for preparing the low-emissivity coated glass, the method comprising the following steps:
[0082] (1) Glass pretreatment: Clean the ultra-clear glass to remove dust, oil and other impurities.
[0083] (2) Loading glass: Load the pre-treated ultra-white glass into the vacuum chamber of the magnetron sputtering equipment.
[0084] (3) Vacuuming: Start the vacuum system and evacuate the vacuum chamber to 5×10 -6 Pa.
[0085] (4) Target preparation: Install and prepare the various targets used to prepare low-emissivity coated glass.
[0086] (5) Pre-sputtering: The target material is pre-sputtered to remove oxides, impurities, etc. on the surface of the target material to ensure the quality of the coating.
[0087] (6) Turn on the magnetron sputtering power supply and sputter-deposit a silicon nitride layer, a zinc tin oxide layer, an aluminum-doped zinc oxide layer, a silver layer, a nickel-chromium layer, an aluminum-doped zinc oxide layer, a nickel-chromium oxide layer, an aluminum-doped zinc oxide layer, a silicon nitride layer, and a zirconium oxide layer on the surface of the ultra-white glass in sequence.
[0088] Among them, the vacuum magnetron sputtering parameters of the silicon nitride layer include: the rotating target material is silicon-aluminum alloy, the working gas includes argon with a flow rate of 450 sccm and nitrogen with a flow rate of 650 sccm; the vacuum magnetron sputtering parameters of the zinc tin oxide layer include: the target material is zinc tin oxide (composed of 52% ZnO and 48% SnO2), the working gas includes argon with a flow rate of 700 sccm and oxygen with a flow rate of 50 sccm; the vacuum magnetron sputtering parameters of the aluminum-doped zinc oxide layer include: the target material is aluminum-doped zinc oxide, the working gas includes argon with a flow rate of 800 sccm and oxygen with a flow rate of 30 sccm; the vacuum magnetron sputtering parameters of the silver layer include: Including: the target material is silver, and the working gas is argon with a flow rate of 200sccm; the vacuum magnetron sputtering parameters of the nickel-chromium layer include: the target material is nickel-chromium alloy (composed of 20% Ni and 80% Cr), and the working gas is argon with a flow rate of 600sccm; the vacuum magnetron sputtering parameters of the nickel-chromium oxide layer include: the target material is nickel-chromium alloy (composed of 80% Ni and 20% Cr), and the working gas includes an inert gas with a flow rate of 10sccm and an oxygen with a flow rate of 2sccm; the vacuum magnetron sputtering parameters of the zirconium oxide layer include: the target material is zirconium oxide, and the working gas includes argon with a flow rate of 800sccm and an oxygen with a flow rate of 20sccm.
[0089] (7) After the sputtering deposition is completed, the gas is slowly released to atmospheric pressure, and the low-emissivity coated glass is transported out through a roller conveyor.
[0090] Example 2
[0091] This embodiment provides a low-emissivity coated glass, the low-emissivity coated glass comprising:
[0092] The glass substrate is ultra-white glass.
[0093] A low-emissivity film comprises a stacked silicon nitride layer, a zinc tin oxide layer, an aluminum-doped zinc oxide layer, a silver layer, a composite protective layer, a silicon nitride layer and a zirconium oxide layer in a direction away from the glass substrate.
[0094] The composite protective layer includes a nickel-chromium layer, an aluminum-doped zinc oxide layer, a nickel-chromium oxide layer and an aluminum-doped zinc oxide layer which are stacked in a direction away from the silver layer.
[0095] Among them, the thickness of the silicon nitride layer is 20nm, the thickness of the zinc tin oxide layer is 25nm, the thickness of the aluminum-doped zinc oxide layer is 8nm, the thickness of the silver layer is 10nm, the thickness ratio of the silver layer, nickel-chromium layer, aluminum-doped zinc oxide layer, nickel-chromium oxide layer and aluminum-doped zinc oxide layer is 10:0.6:8:0.3:8, the thickness of the silicon nitride layer is 25nm, and the thickness of the protective layer is 7nm.
[0096] This embodiment also provides a method for preparing the low-emissivity coated glass, the method comprising the following steps:
[0097] (1) Glass pretreatment: Clean the ultra-clear glass to remove dust, oil and other impurities.
[0098] (2) Loading glass: Load the pre-treated ultra-white glass into the vacuum chamber of the magnetron sputtering equipment.
[0099] (3) Vacuuming: Start the vacuum system and evacuate the vacuum chamber to 5×10 -6 Pa.
[0100] (4) Target preparation: Install and prepare the various targets used to prepare low-emissivity coated glass.
[0101] (5) Pre-sputtering: The target material is pre-sputtered to remove oxides, impurities, etc. on the surface of the target material to ensure the quality of the coating.
[0102] (6) Turn on the magnetron sputtering power supply and sputter-deposit a silicon nitride layer, a zinc tin oxide layer, an aluminum-doped zinc oxide layer, a silver layer, a nickel-chromium layer, an aluminum-doped zinc oxide layer, a nickel-chromium oxide layer, an aluminum-doped zinc oxide layer, a silicon nitride layer, and a zirconium oxide layer on the surface of the ultra-white glass in sequence.
[0103] Among them, the vacuum magnetron sputtering parameters of the silicon nitride layer include: the rotating target material is silicon-aluminum alloy, the working gas includes argon with a flow rate of 450 sccm and nitrogen with a flow rate of 650 sccm; the vacuum magnetron sputtering parameters of the zinc tin oxide layer include: the target material is zinc tin oxide (composed of 52% ZnO and 48% SnO2), the working gas includes argon with a flow rate of 700 sccm and oxygen with a flow rate of 50 sccm; the vacuum magnetron sputtering parameters of the aluminum-doped zinc oxide layer include: the target material is aluminum-doped zinc oxide, the working gas includes argon with a flow rate of 800 sccm and oxygen with a flow rate of 30 sccm; the vacuum magnetron sputtering parameters of the silver layer include: Including: the target material is silver, and the working gas is argon with a flow rate of 200sccm; the vacuum magnetron sputtering parameters of the nickel-chromium layer include: the target material is nickel-chromium alloy (composed of 20% Ni and 80% Cr), and the working gas is argon with a flow rate of 600sccm; the vacuum magnetron sputtering parameters of the nickel-chromium oxide layer include: the target material is nickel-chromium alloy (composed of 80% Ni and 20% Cr), and the working gas includes an inert gas with a flow rate of 10sccm and an oxygen with a flow rate of 2sccm; the vacuum magnetron sputtering parameters of the zirconium oxide layer include: the target material is zirconium oxide, and the working gas includes argon with a flow rate of 800sccm and an oxygen with a flow rate of 20sccm.
[0104] (7) After the sputtering deposition is completed, the gas is slowly released to atmospheric pressure, and the low-emissivity coated glass is transported out through a roller conveyor.
[0105] Example 3
[0106] This embodiment provides a low-emissivity coated glass, the low-emissivity coated glass comprising:
[0107] The glass substrate is ultra-white glass.
[0108] A low-emissivity film comprises a stacked silicon nitride layer, a zinc tin oxide layer, an aluminum-doped zinc oxide layer, a silver-aluminum alloy layer, a composite protective layer, a silicon nitride layer and a zirconium oxide layer in a direction away from the glass substrate.
[0109] The composite protective layer includes a stacked nickel-chromium layer, an aluminum-doped zinc oxide layer, a nickel-chromium oxide layer and an aluminum-doped zinc oxide layer in a direction away from the silver-aluminum alloy layer.
[0110] Among them, the thickness of the silicon nitride layer is 10nm, the thickness of the zinc tin oxide layer is 15nm, the thickness of the aluminum-doped zinc oxide layer is 6nm, the thickness of the silver-aluminum alloy layer is 6nm, the thickness ratio of the silver-aluminum alloy layer, the nickel-chromium layer, the aluminum-doped zinc oxide layer, the nickel-chromium oxide layer and the aluminum-doped zinc oxide layer is 6:1:10:0.8:10, the thickness of the silicon nitride layer is 20nm, and the thickness of the protective layer is 4nm.
[0111] This embodiment also provides a method for preparing the low-emissivity coated glass, the method comprising the following steps:
[0112] (1) Glass pretreatment: Clean the ultra-clear glass to remove dust, oil and other impurities.
[0113] (2) Loading glass: Load the pre-treated ultra-white glass into the vacuum chamber of the magnetron sputtering equipment.
[0114] (3) Vacuuming: Start the vacuum system and evacuate the vacuum chamber to 5×10 -6 Pa.
[0115] (4) Target preparation: Install and prepare the various targets used to prepare low-emissivity coated glass.
[0116] (5) Pre-sputtering: The target material is pre-sputtered to remove oxides, impurities, etc. on the surface of the target material to ensure the quality of the coating.
[0117] (6) Turn on the magnetron sputtering power supply and sputter-deposit a silicon nitride layer, a zinc tin oxide layer, an aluminum-doped zinc oxide layer, a silver-aluminum alloy layer, a nickel-chromium layer, an aluminum-doped zinc oxide layer, a nickel-chromium oxide layer, an aluminum-doped zinc oxide layer, a silicon nitride layer, and a zirconium oxide layer on the surface of the ultra-white glass in sequence.
[0118] Among them, the vacuum magnetron sputtering parameters of the silicon nitride layer include: the rotating target material is silicon-aluminum alloy, and the working gas includes argon with a flow rate of 450 sccm and nitrogen with a flow rate of 650 sccm; the vacuum magnetron sputtering parameters of the zinc tin oxide layer include: the target material is zinc tin oxide (composed of 52% ZnO and 48% SnO2), and the working gas includes argon with a flow rate of 700 sccm and oxygen with a flow rate of 50 sccm; the vacuum magnetron sputtering parameters of the aluminum-doped zinc oxide layer include: the target material is aluminum-doped zinc oxide, and the working gas includes argon with a flow rate of 800 sccm and oxygen with a flow rate of 30 sccm; the vacuum magnetron sputtering parameters of the silver-aluminum alloy layer include: the target material is silver-aluminum alloy (composed of 98% Ag and 2% Al), and the working gas is argon with a flow rate of 200 sccm; the vacuum magnetron sputtering parameters of the nickel-chromium layer include: the target material is a nickel-chromium alloy (composed of 20% Ni and 80% Cr), and the working gas is argon with a flow rate of 600 sccm; the vacuum magnetron sputtering parameters of the nickel-chromium oxide layer include: the target material is a nickel-chromium alloy (composed of 80% Ni and 20% Cr), and the working gas includes an inert gas with a flow rate of 10 sccm and an oxygen with a flow rate of 2 sccm; the vacuum magnetron sputtering parameters of the zirconium oxide layer include: the target material is zirconium oxide, and the working gas includes argon with a flow rate of 800 sccm and an oxygen with a flow rate of 20 sccm.
[0119] (7) After the sputtering deposition is completed, the gas is slowly released to atmospheric pressure, and the low-emissivity coated glass is transported out through a roller conveyor.
[0120] Example 4
[0121] The difference between this embodiment and embodiment 1 is that the thickness of the nickel-chromium layer is adjusted so that the thickness ratio of the silver layer to the nickel-chromium layer is 8:2.
[0122] The rest of the preparation methods and parameters remained the same as in Example 1.
[0123] Example 5
[0124] The difference between this embodiment and embodiment 1 is that the thickness of the nickel-chromium layer is adjusted so that the thickness ratio of the silver layer to the nickel-chromium layer is 8:0.2.
[0125] The rest of the preparation methods and parameters remained the same as in Example 1.
[0126] Example 6
[0127] The difference between this embodiment and embodiment 1 is that the thickness of the nickel-chromium oxide layer is adjusted so that the thickness ratio of the silver layer to the nickel-chromium oxide layer is 8:2.
[0128] The rest of the preparation methods and parameters remained the same as in Example 1.
[0129] Example 7
[0130] The difference between this embodiment and embodiment 1 is that the thickness of the nickel-chromium oxide layer is adjusted so that the thickness ratio of the silver layer to the nickel-chromium oxide layer is 8:0.1.
[0131] The rest of the preparation methods and parameters remained the same as in Example 1.
[0132] Example 8
[0133] The difference between this embodiment and embodiment 1 is that the thickness ratio of the nickel-chromium layer to the nickel-chromium oxide layer is 0.5:1.
[0134] The rest of the preparation methods and parameters remained the same as in Example 1.
[0135] Example 9
[0136] The difference between this embodiment and embodiment 1 is that the thickness ratio of the nickel-chromium layer to the nickel-chromium oxide layer is 1:0.2.
[0137] The rest of the preparation methods and parameters remained the same as in Example 1.
[0138] Comparative Example 1
[0139] The difference between this comparative example and Example 1 is that no nickel-chromium layer is provided.
[0140] The rest of the preparation methods and parameters remained the same as in Example 1.
[0141] Comparative Example 2
[0142] The difference between this comparative example and Example 1 is that the nickel chromium oxide layer is not provided.
[0143] The rest of the preparation methods and parameters remained the same as in Example 1.
[0144] Comparative Example 3
[0145] The difference between this comparative example and Example 1 is that no aluminum-doped zinc oxide layer is provided in the composite protective layer.
[0146] The rest of the preparation methods and parameters remained the same as in Example 1.
[0147] Comparative Example 4
[0148] The difference between this comparative example and Example 1 is that no silicon nitride layer is provided between the composite protective layer and the zirconium oxide layer.
[0149] The rest of the preparation methods and parameters remained the same as in Example 1.
[0150] Performance Testing
[0151] The low-emissivity coated glass obtained in the above embodiment and comparative example was made into a double-chamber insulating glass, comprising a 5mm first glass, a 5mm second glass, and a 5mm third glass. A 12mm gas spacer was formed between the first glass and the second glass, and between the second glass and the third glass. The second glass and the third glass were both the low-emissivity coated glass. The protective layer of the third glass was located on the side close to the second glass. The structure was as follows:
[0152] 5 white glass+12Ar+5Low-E#3+12Ar+5Low-E#5.
[0153] The optical performance tests of the double-chamber insulating glass were carried out, including tests of visible light transmittance T, U value and shading coefficient SC.
[0154] Among them, the test method for visible light transmittance T is the spectrophotometer method; the test method for U value is: GB / T2680-94, and the environmental conditions meet the NFRC100-2010 standard; the test method for shading coefficient SC is the spectrophotometer method.
[0155] The test results are shown in Table 1.
[0156] Table 1
[0157]
[0158] analyze:
[0159] As shown in Table 1, the double-chamber insulating glass produced using the low-emissivity coated glass provided by the present invention has a U-value of ≤0.8 and a building shading coefficient (SC) of ≥0.60, providing excellent thermal insulation. This reduces energy loss in winter, lowering heating costs, and reduces outdoor heat ingress in summer, lowering cooling costs. Furthermore, the visible light transmittance is ≥60%, allowing more visible light to penetrate the window without affecting the field of view, providing excellent daylighting. Therefore, this double-chamber insulating glass meets ultra-low energy consumption requirements and has great potential for application.
[0160] From the comparison between Example 1 and Examples 4-5, it can be seen that if the thickness ratio of the silver layer to the nickel-chromium layer is too small, it is not conducive to the improvement of visible light transmittance; if the thickness ratio of the silver layer to the nickel-chromium layer is too large, it is not conducive to the growth of the film layer and affects the quality of the film layer.
[0161] From the comparison between Example 1 and Examples 6-7, it can be seen that if the thickness ratio of the silver layer to the nickel chromium oxide layer is too small, it is not conducive to the improvement of visible light transmittance; if the thickness ratio of the silver layer to the nickel chromium oxide layer is too large, it is not conducive to the growth of the film layer and affects the quality of the film layer.
[0162] From the comparison between Example 1 and Examples 8-9, it can be seen that if the thickness ratio of the nickel-chromium layer and the nickel-chromium oxide layer is too small, it is not conducive to the improvement of visible light transmittance; if the thickness ratio of the nickel-chromium layer and the nickel-chromium oxide layer is too large, it is not conducive to the growth of the film layer and affects the quality of the film layer.
[0163] From the comparison between Example 1 and Comparative Example 1, it can be seen that if the nickel-chromium layer is not provided, the film quality is affected and the optical performance is poor.
[0164] From the comparison between Example 1 and Comparative Example 2, it can be seen that if the nickel chromium oxide layer is not provided, the film quality is affected and the optical performance is poor.
[0165] From the comparison between Example 1 and Comparative Example 3, it can be seen that if the aluminum-doped zinc oxide layer is not provided in the composite protective layer, the optical performance is poor.
[0166] From the comparison between Example 1 and Comparative Example 4, it can be seen that if the silicon nitride layer is not provided between the composite protective layer and the zirconium oxide layer, the optical performance is poor.
[0167] It should be noted that while the present invention illustrates the process method through the above-described embodiments, the present invention is not limited to the above-described process steps, and does not necessarily rely on the above-described process steps for implementation. Those skilled in the art will appreciate that any improvements to the present invention, equivalent replacements for the raw materials used, additions of auxiliary components, and selection of specific methods, etc., fall within the scope of protection and disclosure of the present invention.
Claims
1. A low-emissivity coated glass, characterized in that: The low-emissivity coated glass includes: glass substrate; A low-emissivity film, wherein the low-emissivity film includes a first dielectric layer, an intermediate layer, a second dielectric layer, an infrared reflective layer, a composite protective layer, a third dielectric layer, and a protective layer stacked in a direction away from the glass substrate; The composite protective layer includes a first protective layer, a second protective layer, a third protective layer and a fourth protective layer which are stacked in a direction away from the infrared reflective layer.
2. The low-emissivity coated glass according to claim 1, characterized in that: The first dielectric layer includes a silicon nitride layer; Preferably, the intermediate layer comprises a zinc tin oxide layer; Preferably, the second dielectric layer comprises an aluminum-doped zinc oxide layer; Preferably, the thickness of the first dielectric layer is 10-20 nm; Preferably, the thickness of the intermediate layer is 15-25 nm; Preferably, the thickness of the second dielectric layer is 6-10 nm.
3. The low-emissivity coated glass according to claim 1 or 2, characterized in that: The infrared reflection layer includes a silver layer or a silver-based alloy layer; Preferably, the infrared reflective layer has a thickness of 6-12 nm.
4. The low-emissivity coated glass according to any one of claims 1 to 3, characterized in that: The first protective layer includes a nickel-chromium layer; Preferably, the second protective layer comprises an aluminum-doped zinc oxide layer; Preferably, the third protective layer comprises a nickel chromium oxide layer; Preferably, the fourth protective layer comprises an aluminum-doped zinc oxide layer; Preferably, the thickness ratio of the infrared reflective layer, the first protective layer, the second protective layer, the third protective layer and the fourth protective layer is (6-12):(0.5-1):(6-10):(0.3-0.8):(6-10); Preferably, the thickness of the first protective layer is 0.5-1 nm; Preferably, the thickness of the second protective layer and the fourth protective layer are each independently 6-10 nm; Preferably, the thickness of the third protective layer is 0.3-0.8 nm.
5. The low-emissivity coated glass according to any one of claims 1 to 4, characterized in that: The third dielectric layer includes a silicon nitride layer; Preferably, the protective layer comprises a zirconium oxide layer; Preferably, the thickness of the third dielectric layer is 20-30 nm; Preferably, the thickness of the protective layer is 4-8 nm.
6. A method for preparing low-emissivity coated glass according to any one of claims 1 to 5, characterized in that: The preparation method comprises the following steps: A vacuum magnetron sputtering method is used to sequentially deposit a first dielectric layer, an intermediate layer, a second dielectric layer, an infrared reflection layer, a composite protective layer, a third dielectric layer and a protective layer on the surface of a glass substrate to form a low-emissivity film; The composite protective layer includes a first protective layer, a second protective layer, a third protective layer and a fourth protective layer which are stacked in a direction away from the infrared reflective layer.
7. The preparation method according to claim 6, characterized in that The vacuum magnetron sputtering parameters of the intermediate layer include: The target material is zinc tin oxide, and the working gas includes an inert gas and oxygen with a flow ratio of (12-16):1; Preferably, the vacuum magnetron sputtering parameters of the first dielectric layer and the third dielectric layer independently include: The target material is silicon aluminum alloy, and the working gas includes inert gas and nitrogen with a flow ratio of 9:(11-15); Preferably, the vacuum magnetron sputtering parameters of the second dielectric layer include: The target material is aluminum-doped zinc oxide, and the working gas includes an inert gas and oxygen with a flow ratio of (24-28):1; Preferably, the vacuum magnetron sputtering parameters of the infrared reflective layer include: The target material is silver or silver-based alloy, and the working gas is inert gas; Preferably, the vacuum magnetron sputtering parameters of the protective layer include: The target material is zirconium oxide, and the working gas includes an inert gas and oxygen with a flow ratio of (35-45):
1.
8. The preparation method according to claim 6 or 7, characterized in that The vacuum magnetron sputtering parameters of the first protective layer include: The target material is nickel-chromium alloy and the working gas is inert gas; Preferably, the vacuum magnetron sputtering parameters of the second protective layer and the fourth protective layer independently include: The target material is aluminum-doped zinc oxide, and the working gas includes an inert gas and oxygen with a flow ratio of (24-28):1; Preferably, the vacuum magnetron sputtering parameters of the third protective layer include: The target material is nickel-chromium alloy, and the working gas includes inert gas and oxygen with a flow ratio of (4-9):
1.
9. A double-chamber insulating glass, characterized in that: The double-chamber insulating glass comprises a first glass, a second glass and a third glass, wherein a gas spacer layer is formed between the first glass and the second glass and between the second glass and the third glass; Wherein, the second glass and the third glass are each independently the low-emissivity coated glass according to any one of claims 1 to 5, and the protective layer of the third glass is located on a side close to the second glass.
10. Use of the low-emissivity coated glass according to any one of claims 1 to 5 or the double-chamber insulating glass according to claim 9 in the field of architecture or new energy vehicles.